MEDLINE on CD-ROM: A Comparison of DIALOG OnDisc and Silver Platter Interface - Kottai, A. (Journal of Information and Knowledge, 1993)
A comparison of DIALOG On Disc and Silver Platter interfaces in relation to MEDLINE is made. The CD-ROM technology, hardware requirements, installation procedures, scope, cost, terms, searching the system, displaying and printing search results, documentation and user support given by them are discussed in this paper.